ON THE POSSIBILITY OF ANALYTICAL DETERMINATION OF STRUCTURALLY BOUND GOLD IN SULFIDE MINERALS - Tauson V.L.; Salikhov A.; Matshullat J.; Smagunov N.V.; Bessarabova O.I.; Menshikov V.I.; Parkhomenko I.Y. (My University, 2001)
The idea of a statistical analysis of the distribution of hydrothermally synthesized single sulfide crystals using their gold contents is developed specifically to distinguish the structurally bound gold component. Mercury was taken as a model example. Similar to gold, mercury shows reduction-aided chemosorption on sulfides, but its speciation can be directly determined by thermal atomic absorption analysis. It was ascertained that the structurally bound component is best characterized by a set of the lowest values of element concentrations with a variation coefficient no higher than 20% (not accounting for the random error of determination). Proceeding from this result and from previous data on Au distribution, a scheme was elaborated to process the analytical results for individual crystals in order to characterize the structurally bound Au component. The main requirement for the analytical method-a combination of a low detection limit and high accuracy-is met by atomic absorption spectrometry with electrothermal atomization of liquid or solid samples. The optimum conditions of analysis were determined for sulfide minerals (pyrite, galena, and greenockite). Some modifications of the method were compared, which demonstrated a reasonable agreement for both low and high Au contents. The application of the method of direct Au determination in solid samples revealed difficulties in the determination of the structurally bound Au component at high Au concentrations close to the saturation limit, and it was necessary to analyze fragments of crystalline individuals. A more promising variant of the experimental procedure includes the investigation of phase correspondence in gold-bearing systems with Au-undersaturated minerals. The perspectives of the direct determination of Au speciation by the method of a stepwise increase of atomization temperature of solid samples are discussed.